2016
DOI: 10.1080/17520843.2016.1148754
|View full text |Cite
|
Sign up to set email alerts
|

Size, value and momentum in stock returns: evidence from India

Abstract: This paper examines the effects of size, value and momentum on the cross-sectional relation between expected returns and risk in the Indian stock market. We find that the conditional Carhart four-factor model empirically describes the variation of crosssection of return better than the unconditional model. When size, book-to-market and momentum effects are controlled in the conditional model, the positive relation of market beta, book-to-market and momentum with expected returns remains economically and statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Every year, P/B ratio is based on the closing prices of the stocks and number of paid up equity shares as at March end. It is customary in literature to use 6-month lagged values of variables for portfolio creation (Agarwalla, Jacob & Varma, 2013; Das & Barai, 2016). This is to ensure that the variables are known at the time of portfolio creation.…”
Section: Objectives Data and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Every year, P/B ratio is based on the closing prices of the stocks and number of paid up equity shares as at March end. It is customary in literature to use 6-month lagged values of variables for portfolio creation (Agarwalla, Jacob & Varma, 2013; Das & Barai, 2016). This is to ensure that the variables are known at the time of portfolio creation.…”
Section: Objectives Data and Methodologymentioning
confidence: 99%
“…While Claessens et al (1995) reported insignificant ratio of book-to-market (B/M) premium, de Groot and Verschoor, 2002; Mohanty, 2002 and Kumar and Sehgal, 2004 reported weak evidence of the value effect. Significant effect was reported by Barry et al, 2002; Sehgal, Subramaniam and Morandiere, 2012; Sehgal and Balakrishnan, 2013; Aziz and Ansari, 2014; Ebrahim et al, 2014; Sehgal and Pandey, 2014 and Das and Barai, 2016. Taneja (2010) reported a high correlation between the size and value factors and hence argued that either of the two factors could explain the variability in stock returns.…”
Section: Literature Reviewmentioning
confidence: 98%
“…It is based on number of paid-up equity shares as at March-end and closing prices as at September-end of the same year. It is customary in literature to employ six months gap between fiscal year-end and computation of variables [44] [45] [46]. This is to avoid look-ahead bias 1 and ensure that the variables are known at the time of computation.…”
Section: Objective Data and Methodologymentioning
confidence: 99%
“…The study conducted by Das & Barai (2016) provides evidence in literature which proves beta to be instable over time, stating that it can only be estimated as it is unobservable due to its dynamics. The study attempts to measure industry beta in Indian market and found that market risk of industry is sensitive to changes in global market.…”
Section: Literature Review and Theory Formationmentioning
confidence: 99%